Thermoactivated current spectroscopy of polyethylene terephthalate films irradiated by heavy xenon ions - Gorokhovatsky Yuriy (St. Petersburg Polytechnical University Journal: Physics and Mathematics, 2021)
The paper analyzes the electret state of polyethylene terephthalate (PET) films irradiated on the IC-100 cyclotron (JINR LAR) using thermostimulated spectroscopy methods. Thermally stimulated discharge currents (thermally stimulated depolarization) of PET film samples obtained at different technological stages of track membrane manufacturing are studied. The results of the analysis of thermally stimulated depolarization currents indicate a significant change in the spectra of the energy states of the electric charge accumulated during the polarization of PET films, during irradiation with accelerated heavy Xe ions, ultraviolet treatment, and alkaline etching of latent tracks. The parameters of relaxation processes (activation energy and effective frequency factor) occurring in track membranes are calculated using the Eyring method. A significant change in the energy state spectra of the electric charge accumulated during the polarization of PET films as a result of ion-track processes in them indicates the possibility of creating an electret state in PET films and track membranes irradiated with heavy ions on their basis.